2021
DOI: 10.22271/oral.2021.v7.i2c.1204
|View full text |Cite
|
Sign up to set email alerts
|

Mineral trioxide aggregate and areas of its use in dentistry: A literature review

Abstract: Mineral trioxide aggregate is a biocompatible dental material consisting of thyroxide powder and hydrophilic particles. In addition to their dentinogenic and osteogenic potentials, it also exhibits good sealing properties. It has a wide range of areas of use in endodontic and restorative dentistry. In clinical practice, it is a material of choice in many applications such as repair of perforations, root-end fillings, apexhivation and regenerative endodontic treatment procedures, vital pulp treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…21,22 The highest success rates in the MTA group can be explained by its sealing ability, and mechanical and chemical stability. 23,24 The disadvantages of MTA, however, are its high cost, long setting time, difficult handling, and tooth discoloration. 10 A previous study 6 reported similar success rates at the 6th, 12th, and 24th month for partial pulpotomy with MTA, aligning with our study despite procedural differences.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 The highest success rates in the MTA group can be explained by its sealing ability, and mechanical and chemical stability. 23,24 The disadvantages of MTA, however, are its high cost, long setting time, difficult handling, and tooth discoloration. 10 A previous study 6 reported similar success rates at the 6th, 12th, and 24th month for partial pulpotomy with MTA, aligning with our study despite procedural differences.…”
Section: Discussionmentioning
confidence: 99%